2005
DOI: 10.1210/jc.2005-0385
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of Sensorineural Hearing Loss in Men Born Small for Gestational Age with and without Obesity or Height Catch-Up Growth: A Prospective Longitudinal Register Study on Birth Size in 245,000 Swedish Conscripts

Abstract: The thrifty phenotype hypothesis also seems to be valid for SNHL, meaning that SNHL in adulthood may originate from events during fetal life. SNHL might be a new clinical feature of the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 24 publications
5
56
0
Order By: Relevance
“…Barrenas also demonstrated an association between overweight and obesity and sensori-neural hearing impairment (SNHI) especially if born light for gestational age. These results were broadly consistent with SNHI resulting from mechanisms suggested by the thrifty phenotype hypothesis, with SNHI as a possible clinical feature of the metabolic syndrome (Barrenas et al 2005b).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Barrenas also demonstrated an association between overweight and obesity and sensori-neural hearing impairment (SNHI) especially if born light for gestational age. These results were broadly consistent with SNHI resulting from mechanisms suggested by the thrifty phenotype hypothesis, with SNHI as a possible clinical feature of the metabolic syndrome (Barrenas et al 2005b).…”
Section: Introductionsupporting
confidence: 87%
“…Fransen also found that taller people had, on average, better hearing, replicating a previous finding by Barrenas (Barrenas et al 2003(Barrenas et al , 2005a. In a separate study, Barrenas found an association between being born short or light for gestational age and higher hearing threshold levels at age 17-24yrs among Swedish male conscripts (Barrenas et al 2005b). Barrenas also demonstrated an association between overweight and obesity and sensori-neural hearing impairment (SNHI) especially if born light for gestational age.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…It seems unlikely that an increased stature has a generalized adverse effect on the peripheral nerve function, since sensorineural hearing loss, another form of peripheral deficit, by contrast, is associated with a reduced stature (Barrenas et al,) [31]. A short stature is associated with CVS disease, hypertension, early arterial stiffening, IGT, type 2 DM, GDM and pre-eclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Although prematurity and low birthweight are known to be associated with congenital hearing loss, the causal pathway has not been clearly delineated. One study in Atlanta showed elevated relative risks of bilateral sensorineural hearing impairment among children with lower birthweights: prevalence was 0.4/1000 in children weighing ≥4000 g, compared with 1.27/1000 for 1500-1499 g and 5.1/1000 for those <1500 g (Barrenas et al 2005b) and in males of short stature (Barrenas et al 2005a). This interesting finding has led to the hypothesis that fetal programming arising from intrauterine growth retardation might result in delayed cell cycles during development of the cochlea which eventually leads to development of SNHL in adulthood (Niskar et al 2001).…”
Section: Environmental Causes Of Hearing Lossmentioning
confidence: 99%